Response to the COVID-19 Pandemic: Comparison of Strategies in Six Countries - Chen, Haiqian; Shi, Leiyu; Zhang, Yuyao; Wang, Xiaohan; Jiao, Jun; Yang, Manfei; Sun, Gang (Frontiers in Public Health, 2021)
Objective: This study aimed to examine the effectiveness of containment strategies and mitigation strategies to provide a reference for controlling the ongoing global spread of the pandemic. Methods: We extracted publicly available data from various official websites between January 1 and December 31, 2020, summarized the strategies implemented in China, South Korea, Singapore, the United States, the United Kingdom, and France, and assessed the effectiveness of the prevention and control measures adopted by these countries with the daily new cases and mortality rate per 100,000 population. Results: China, South Korea, and Singapore adopted containment strategies, which maintained a proactive approach by identifying and managing cases, tracking and isolating close contacts. China and Singapore had a similar epidemic curve and the new daily cases. As of December 31, 2020, the new daily cases of China and Singapore were below 100 with the mortality rates per 100,000 population of 0.3 and 0.5, respectively. But the new daily case of South Korea was as high as 1,029, with a mortality rate per 100,000 population of 1.8. In contrast, the United States, the United Kingdom, and France responded with mitigation strategies that focus on treating severe cases and those with underlying conditions. They had similar epidemic curves and mortality rates per 100,000 population. The United States had up to 234,133 new confirmed cases per day, and the mortality rate per 100,000 population was 107, while the United Kingdom had 56,029 new confirmed cases per day and the mortality rate per 100,000 population was 108, and France had 20,042 new cases per day, with a mortality rate per 100,000 population of 99. Conclusions: China, Korea, and Singapore, which implemented strict containment measures, had significant outbreak control. Meanwhile, the successful practices in China, Singapore, and South Korea show that the containment strategies were practices that work especially at the individual level identifying and managing the infected patients and their close contacts. In the United States, the United Kingdom, and France, which implemented the mitigation policies, the effect of epidemic prevention and control was not significant that the epidemic continued or even increased epidemic relatively quickly.